A study of outcome of non-operative versus operative management in 50 cases of appendicular lump - Ram, Kamlesh R.; Chandana, Sanjog; Koshti, Sameep (International Surgery Journal, 2017)
Background: Appendicitis is the most common cause of pain requiring surgery. The objective of this study was to compare the different modes of management of appendicular lump whether traditional emergency operation or non-operative management. Methods: This is a retrospective observational study of total 50 cases of complicated appendicitis with appendicular lump/abscess. 18 patients were treated for emergency operations and rest were treated non-operatively with antibiotics alone (n=26) and antibiotics with percutaneous drainage (n=6). 24 patients who were treated non-operatively later on planned for interval operations. Results: The mean age of the patients was 50.8 years, and the ratio of men to women was 27:23. Among them, the emergency surgery (operative) group included 18 patients (36%) and the non-operative treatment group included 32 patients (64%). Duration of symptoms was 7 days in group 1 compared to 9 days in group 2. White blood cells count was similar in both groups. During emergency surgery, three patients (15%) require resection, whereas none underwent in planned group. Duration of surgery was 115 and 100 min in emergency and planned groups, respectively. The complication rate was higher almost twice in emergency group compared to planned group. The hospital stay was 12 and 19 days in emergency and planned groups, respectively. Conclusions: Therefore, as treatment for appendicitis associated with an abscess or mass, the decision whether to perform initial emergency surgery or to perform non-operative managements, and if non-operative managements are performed, whether to perform interval surgery after a certain period or to perform only the ambulatory follow-up observation depends on the surgeon’s overall evaluation of the clinical features of the individuals.